Health, Climate Change and Sustainability: A systematic Review and Thematic Analysis of the Literature - A. Nichols; V. Maynard; B. Goodman; J. Richardson (SAGE Publishing, 2009)
Background Evidence of climate change and its impact continues to be accumulated, and it is argued that the consequences of climate change are likely to result in an increased demand on health services. It has been claimed that climate change presents new challenges for health services and that strategies should be adopted to address these challenges. Aim The aim of this systematic review was to map published literature on health, climate change and sustainability by categorising papers according to their focus on effects, strategy and actions, and to provide a thematic analysis of their content. Methods Systematic searches were conducted via a range of healthcare related databases i.e. Pubmed, Medline, CINAHL, AMED, ASSIA, IBSS and ISI Web of Knowledge. Searches focussed upon papers published in English between 1998 and 2008. Retrieved papers were studied by the authors in order to inform the thematic analysis of their content. Results A total of 114 publications were retrieved, of which 36 met the inclusion criteria for the systematic review. These 36 publications were categorised and are discussed according to their focus on: effects/impacts, strategy/policy, action/examples. Conclusions A number of papers report the potential health effects of climate change while others report policies and strategies to tackle these effects. However there is an urgent need to identify and report on the implementation of strategies to mitigate and adapt to these challenges and to publish real examples of actions. Actions that are taken need to be evidence/policy based, and implementations monitored, evaluated and published.